Electronic processing of personal data between the sanctity of privacy and criminal protection (Damascus University Journal for legal sciences, 2025)
Information technology has begun to be used as an advanced technology in controlling, collecting, processing, storing, retrieving and making use of data. It has become commonplace to transfer this data via electronic networks, and the world has become more like a large society in which means of information technology and various communication networks are interconnected, and personal data flows between its parts.Accordingly, information technology and communication networks contain a huge amount of personal data, and in this huge environment, monitoring and control are weakened, which increases the risks of attacking this data. Consequently, electronic progress and increasing reliance on information technology means to manage societal affairs have been accompanied by risks based on illegal access to personal data and its misuse, which affects the privacy of individuals.This research is related to studying the penal policy adopted by the Syrian legislator in protecting personal data through Law No. 12 of 2024 regarding the protection of personal data, and the extent of divergence and convergence between the basis of penal protection stipulated in this law, and the protection of data through other laws, the most important of which is the law regulating Communication on the network, combating cybercrime, and the Civil Status Law, let us reach the end of our research to determine the suitability of the Syrian legislator’s penal policy in achieving adequate protection for this data in a way that ensures preserving the sanctity of people’s privacy.
Keywords: Electronic processing; Criminal Protection